2017
DOI: 10.1111/rec.12499
|View full text |Cite
|
Sign up to set email alerts
|

Plantation age, understory vegetation, and species‐specific traits of target seedlings alter the competition and facilitation role of Eucalyptus in South China

Abstract: The Chinese government is considering ways to reconstruct Eucalyptus plantation monocultures in order to improve their ecosystem services. However, the effects of competition or facilitation of Eucalyptus on native species during the reconstruction have not been identified, especially during the formation of novel ecosystems. To better understand these relationships, in this study we tested the effects of competition and facilitation of Eucalyptus on three target species (Schima superba, Michelia macclurei, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 57 publications
1
9
0
Order By: Relevance
“…Previous studies have shown that very shade-tolerant species lack alternative mechanisms to cope with excess light energy and are more likely to incur photoinhibitory damage to their photosynthetic apparatus (Rodrıǵuez-Calcerrada et al, 2006). Therefore, C. fissa seedlings had a distinct photoinhibition which reduced carbon assimilation and growth under high radiation in open sites (Yang et al, 2010;Sun Z. et al, 2017). In agreement with the previous studies (Uriarte et al, 2004;Wang et al, 2012;Pu et al, 2017), we found a significantly positive relationship between initial size and seedling survival ( Figures 4A-E).…”
Section: Species Identity and Initial Size Were Drivers Of Seedlings supporting
confidence: 91%
See 1 more Smart Citation
“…Previous studies have shown that very shade-tolerant species lack alternative mechanisms to cope with excess light energy and are more likely to incur photoinhibitory damage to their photosynthetic apparatus (Rodrıǵuez-Calcerrada et al, 2006). Therefore, C. fissa seedlings had a distinct photoinhibition which reduced carbon assimilation and growth under high radiation in open sites (Yang et al, 2010;Sun Z. et al, 2017). In agreement with the previous studies (Uriarte et al, 2004;Wang et al, 2012;Pu et al, 2017), we found a significantly positive relationship between initial size and seedling survival ( Figures 4A-E).…”
Section: Species Identity and Initial Size Were Drivers Of Seedlings supporting
confidence: 91%
“…Previous studies have shown that very shade-tolerant species lack alternative mechanisms to cope with excess light energy and are more likely to incur photoinhibitory damage to their photosynthetic apparatus ( Rodríguez-Calcerrada et al., 2006 ). Therefore, C. fissa seedlings had a distinct photoinhibition which reduced carbon assimilation and growth under high radiation in open sites ( Yang et al., 2010 ; Sun Z. et al., 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…We evaluated plantations and native forests beyond black and white perspectives in order to provide insights for developing multifunctional landscape forests. For instance, these forests can be developed to guide toward a species selection for mixed-species systems of native species within Eucalyptus plantations [39] or manage plantations as nurse systems for restoration purposes [40,41]. This is crucial, especially for countries with landscapes where Eucalyptus plantations are already widely established and acknowledged as an important economic sector by national stakeholders [38,42].…”
Section: Discussionmentioning
confidence: 99%
“…This could be accomplished by interplanting with indigenous tree species such as Betula alnoides, Schima superba, Michelia macclurei, and Castanopsis fissa (Sun, Huang, Yang, Schaefer, & Chen, 2017;Williams, 2015). This could be accomplished by interplanting with indigenous tree species such as Betula alnoides, Schima superba, Michelia macclurei, and Castanopsis fissa (Sun, Huang, Yang, Schaefer, & Chen, 2017;Williams, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…In the long term, the current management should be converted from stand level with pure plantations under successive short-rotations into landscape level with mixed plantations under short-, medium-and long-term cyclic rotations. This could be accomplished by interplanting with indigenous tree species such as Betula alnoides, Schima superba, Michelia macclurei, and Castanopsis fissa (Sun, Huang, Yang, Schaefer, & Chen, 2017;Williams, 2015). We especially recommend high-value native tree species such as Castanopsis hystrix, Dalbergia odorifera and Parashorea chinensis .…”
Section: Discussionmentioning
confidence: 99%